2023
DOI: 10.26633/rpsp.2023.76
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 mortality in two waves of the pandemic in Cali, Colombia, before and during vaccination roll-out

Carlos Reina,
Pablo Roa,
Anthony Garcés
et al.

Abstract: Objective. To describe the variation in COVID-19 mortality among residents of Cali, Colombia, in the second wave of the pandemic, before vaccines, and in the fourth wave, with vaccination roll-out in process, taking into account variables of sex, age group, comorbidities, and interval between onset of symptoms and death, and to estimate the number of deaths averted by vaccination. Methods. A cross-sectional study of second wave and fourth wave deaths and vaccination coverage. The frequencies of attributes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…It is important to account for the variations in costs observed during different periods of our study. Notably, February coincided with the onset of the second wave of the pandemic 16 in Colombia, a phase marked by significant uncertainty surrounding treatment protocols. This uncertainty may have contributed to the higher utilisation of resources during this period.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to account for the variations in costs observed during different periods of our study. Notably, February coincided with the onset of the second wave of the pandemic 16 in Colombia, a phase marked by significant uncertainty surrounding treatment protocols. This uncertainty may have contributed to the higher utilisation of resources during this period.…”
Section: Discussionmentioning
confidence: 99%
“…The first wave peaked in August 2020, the second wave peaked in January 2021, the third wave, the most severe and prolonged, associated with the Delta variant and the emergence of the Mu variant (first identified in Colombia by our group) [ 5 ], peaked in June 2021, and the fourth wave peaked in January 2022. [ 6 ] The present study focuses on the fourth wave, which occurred in mid-January 2022 and reached a maximum mortality rate of 282 deaths per day on 28 January. The Colombian National Institute of Health (INS) reported that 80% of these deaths were attributed to the Omicron variant [ 7 , 8 ], which was designated as a VOC by the WHO on 26 November 2021 [ 9 ].…”
Section: Introductionmentioning
confidence: 99%